Increasing Added Value in Basalt Rocks for Making Basalt Fiber - Yuliadi; Zaenal; Moralista, Elfida; Prabowo, Jerry Dwifajar; Noufal Abhinaya (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2024)
Andesite and basalt are generally mined materials used only for building (construction). To increase the added value, basalt rock is currently starting to be widely used as a construction material that is converted into composites with fiber reinforcement. In this initial research, the aim is to examine the characteristics of basalt rock at three locations in the Greater Bandung area (Gunung Bohong, Cipatik, and Batu Templek), including its chemical composition, physical and mechanical properties, and mineral composition. The research methodology is carried out on three rock characteristics that can be used as basalt fiber, namely the XRF method to determine chemical composition (Al2O3 and SiO2), physical and mechanical testing, as well as the petrographic analysis method to discover mineral composition by examining the presence of Plagioclase minerals. The results of the chemical analysis of all samples are suitable, but there are chemical compounds that do not match the parameters, namely Fe2O3 + FeO and MgO. Samples from Cipatik and Batu Templek are suitable. The physical properties test is also suitable. For mechanical property testing, only samples from Gunung Bohong and Cipatik are suitable. Petrographic tests conclude that the three rock samples fit into the basaltic andesite rock category.